Factors affecting the adoption of rice certified seed technology in selected Barangays in Pototan, Iloilo - Laud, Marie Girlie R.
A study to determine the factors that affect the adoption of rice certified seed technologyintroduced by the Department of Agriculture was conducted among selected farmers in Pototan, Iloilo. The stratified random sampling was used in selecting the respondents who were classified as: 1) those purely using rice certified seed, and 2) those who use certified seeds but not on a regular basis. The collected data was collated, analyzed,and interpreted. Frequently counts, percentages, and central tendencies were used for descriptive in data analyses. This study reveals that the respondents are adopting the rice certified seed technology because of the following reasons ranked by priority: 1) the seed varieties are high yielding, 2) the seed are resistant to pests and diseases, 3) the rice produced has good eating quality, 4) credibility of seed inspectors who inspect the crop stand and analyze for the certification of seeds as well as, the credibility of the seed growers, 5) the rice varieties require shorter number of days to mature, 6) price of certified seeds is affiordable,and 7) the preferred variety of seeds is readily available. The respondents claim several benefits derived from the adoption of rice certified seed technology: 1) increased in the volumes of production; followed by 2) an increase in profit; 3) the cost of pesticides was reduced; 4) high quality milled rice was achieved; and 5) the cost on weeding operation was reduced. Furthermore, the respondents who have adopted the technology claim that they have wider options in selling the seeds. Seeds arising out of certified seeds fetch a higher price that those produce as unprocessed palay. On the other hand, the non-regular users of the technology revealed that they were constrained to use the rice certified seeds regularly because of the high cost it entails which require a bigger amount of investment. Moreover, these non-regular users encountered bad experiences such as low germination percentage of seeds, and the uncertainty of the seed growers credibility. There are two critical factors that affect the adoption of rice certified seed technology in Pototan, Iloilo and these are 1) the educational background and 2) the farm size. The higher the level of education attained, the higher the level of awareness on the quality of seeds to prefer. Also, the bigger the farm size, the more that they will be inclined to use higher seed classification like certified seeds. It is worthwhile to consider therefore that the adoption of rice certified seed technology must be promoted among farmers with higher level of educational attainment and with bigger farm size. Furthermore, in developing a rice production technology, a prime consideration must be the capital requirement for the farmers that should not be intensive so as to enable them to consider favorably the adoption of such technology. The Rice Seed Action Program being implemented by the Department of Agriculture promotes the use of the rice certified seed technology. continuing the program can address the issues brought forward by the non-regular users of certified seeds such as low germination percentage of seeds and the uncertainty of the seed grower's credibility.